Pemanfaatan Pojok Literasi Sekolah dalam Gerakan Literasi Sekolah Dasar Negeri 3 Bandungrejo - Sunuyeko, Nurcholis; Dian Fitri Argarini; Patricia, Firda Alfiana; Wafa, Muhammad Ali; Lailahtus S, Vivi Nur (Yayasan Literasi Sains Indonesia, 2022)
The point in this community service activity (PKM) is to improve the quality of literacy through the Literacy Movement. This activity was carried out at SDN 3 Bandungrejo during September to December 2021. The targets of service include teachers, students, and parents/guardians. The method used is the use of the literacy corner in assisting the Literacy Movement. The service program is structured based on the problems found during the observation process. The absence of libraries as literacy facilities encourages the development of the School Literacy Corner program to improve the quality of literacy, especially the numeracy literacy of students. In addition, it was found that two students in fourth grade and one student in third grade were not fluent in reading. In maintaining the sustainability of the program, this service involves several parties, namely teachers, parents, and the literacy driving community. The existence of collaboration between parties makes this activity successful and sustainable in improving student literacy